Profiling the proteome complement of the secretion from hypopharyngeal gland of Africanized nurse-honeybees (Apis mellifera L.) - Santos, K. S.; dos Santos, L. D.; Mendes, M. A.; de Souza, B. M.; Malaspina, O.; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2005)
The protein complement of the secretion from hypopharyngeal gland of nurse-bees (Apis mellifera L.) was partially identified by using a combination of 2D-PAGE, peptide sequencing by MALDI-PSD/MS and a protein engine identification tool applied to the honeybee genome. The proteins identified were compared to those proteins already identified in the proteome complement of the royal jelly of the honey bees. The 2D gel electrophoresis demonstrated this protein complement is constituted of 61 different polypepides, from which 34 were identified as follows: 27 proteins belonged to MRJPs family, 5 proteins were related to the metabolism of carbohydrates and to the oxido-reduction metabolism of energetic Substrates, I protein was related to the accumulation of iron in honeybee bodies and I protein may be a regulator of MRJP-1 oligomerization. The proteins directly involved with the carbohydrates and energetic metabolisms were: alpha glucosidase, glucose oxidase and alpha amylase, whose are members of the same family of enzymes, catalyzing the hydrolysis of the glucosidic linkages of starch; alcohol dehydrogenase and aldehyde dehydrogenase, whose are constituents of the energetic metabolism. The results of the present manuscript support the hypothesis that the most of these proteins are produced in the hypoharyngeal gland of nurse-bees and secreted into the RJ. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africanized Apis mellifera; royal jelly; peptide mass fingerprints; proteome; MALDI-TOF